Крем’яні знаряддя верхньопалеолітичної стоянки Радомишль І: типологічна специфіка та її інтерпретація - Кононенко, О.М. (Археологія і давня історія України, 2015)
Подано техніко-технологічну і типологічну характеристику колекції крем'яних знахідок із стоянки Радомишль І доби верхнього палеоліту. Характеристика і статистичний аналіз знарядь разом з археозоологічними даними уможливили окреслити виробничу специфіку комплексу. Верхнепалеолитическая стоянка Радомышль I известна с 1950-х гг. И.Г. Шовкопляс определил её как самую раннюю стоянку верхнего палеолита Восточной Европы. Его вывод был основан на наличии в верхнепалеолитической коллекции отдельных так называемых мустьерских элементов (радиальных нуклеусов, остроконечников, скребел). Проведенный анализ типологического состава кремневой коллекции Радомышля I, а также выводы Ю.Е. Демиденко и В.И. Усика о ее технико-технологической специфике опровергают традиционное мнение об отнесении памятника к переходному периоду от среднего к верхнему палеолиту. Также нет основанийсвязывать индустрию Радомышля I с ориньякским технокомплексом из-за единичности в ней ведущих ориньякских форм. Кременная коллекция Радомышля I вполне соответствует основным критериям средней поры верхнего палеолита. Этому не противоречат и обе его даты 14С (Оха-697: 19000 ± 300 BP и Ki-6210: 19600 ± 350 В Р). Соответственно, с большей вероятностью он относится к памятникам граветтского круга. Невозможность более точной культурно-хронологической интерпретации Радомышль I связана с отсутствием в его инвентаре наиболее информативных в этом аспекте орудий — вкладышей дистанционного охотничьего оружия. Специфика кремневой коллекции памятника, выраженная в большом количестве орудий (15 %), преобладании резцов и ретушированных пластин, объясняется его узкой ярко выраженной хозяйственной специализацией. Состав кремневых и фаунистических находок свидетельствует, что основной деятельностью жителей стоянки было накопление, сортировка и обработка костей мамонта. Ранее свидетельства такой деятельности фиксировались или на осенне-зимних поселениях со стационарными жилищами из костей мамонта, или в весенне-летних охотничьих лагерях. Археозоологический анализ костей мамонта и их планиграфическое распределение не подтверждает гипотезу о существовании в Радомышле І стационарных жилищ. Также вызывают сомнения наличие здесь другого структурного элемента стационарных поселений — ям. Поэтому Радомышль І следует интерпретировать как место многократного пребывания группы людей, в теплое время года собиравших сухие кости мамонта и обрабатывавших их сделанными на месте кремневыми орудиями. The Upper Palaeolithic site Radomyshl’ I has been known since the 1950s. I.G. Shovkoplyas classified Radomyshl’ I as the earliest Upper Palaeolithic site in the Eastern Europe, i.e. transitional from the Middle to the Upper Palaeolithic. His conclusion was based on the presence of so-called Mousterian elements (radial cores, side-scrapers) within a general Upper Palaeolithic collection. In the 1980s Y. Demidenko and V. Usik have analyzed cores and proved the absence of Mousterian technology in primary flaking and blank production. The blade reduction strategy is clearly Upper Palaeolithic, which based on crest preparation and soft hammer. The absence of Mousterian technology suggests it is unlikely to represent a transitional assemblage, i. e. the oldest Upper Palaeolithic site in the region. Here, I present a new assessment of the typological character of the assemblage. Attribution of the Radomyshl’ I lithic assemblage to the Aurignacian technocomplex, as done often in the past, cannot be confirmed too. Our detailed typological analysis demonstrates there are practically no carinated types in tool-kit. Only three burins out of 800 examples can be classified as carinated burins. Tools with so-called Aurignacian retouch are not numerous too. The tool-kit is dominated by burins (45 %), of which dihedral ones are most frequent. Points on blades with bilateral dorsal retouch and borers represent a quite a significant proportion of the tool kit. Apart of retouched blades / flakes other types such as end-scrapers, combined tools (burin / end-scrapers), denticulates / notches, are represented in small numbers only. At the same time no backed tools were found in the collection. From the observation of common technical and typological characteristics the Radomysl’ I assemblage is more close to the Gravettian techno-complex than any other known in Ukraine. Therefore, we propose to consider Radomyshl’ I as a version of the Eastern European Gravettian. This assessment is supported by 14C dates (OxA-697: 19000 ± 300 BP and Ki-6210: 19600 ± 350 BP), based on which Radomysl’ I cannot belong to the early period of the Upper Paleolithic. At the same time Radomysl’ I has original features and can represent a local variant of the Gravettian cultural tradition. The specific typological structure of the lithic tool kit can be explained by narrow economic specialization. The faunal and lithic remains together suggest that the main activity of inhabitants the Radomyshl’ I was storage, sorting and cutting of mammoth bones.